2015
DOI: 10.1016/j.tifs.2015.05.001
|View full text |Cite
|
Sign up to set email alerts
|

Genetically modified animals: Options and issues for traceability and enforcement

Abstract: Please cite this article as: Lievens, A., Petrillo, M., Querci, M., Patak, A, Genetically modified animals: options and issues for traceability and enforcementAbstract 7The past two decades have witnessed the rise of commercial crops that have been genetically modified for an increased suitability in extensive cultivation. Currently, a substantial body of research is being carried out in order to produce Genetically Modified (GM) animals that may similarly yield improvements in animal breeding, genetics and re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 60 publications
0
24
0
1
Order By: Relevance
“…Thus far, efforts in editing the genome of livestock have mostly concentrated on largely uncontroversial human health applications, such as generating animal models of human genetic diseases, producing biopharmaceuticals and xenotransplantation. However, genomic and other advances are uncovering a growing list of putative target genes and mutations for which editing has been or is being pursued in order to improve aspects of livestock production 175,178,179 , such as growth rate, muscle mass, meat fat content, milk composition, wool growth, resistance to bacterial, viral and parasitic diseases, temperature tolerance, animal welfare and environmental impact (TAble 3). A specific application that is worth mentioning is the generation of malespecific double-muscling by inserting a trans-acting inhibitor of MSTN on the Y chromosome, which could have a major economic impact by improving the carcass yield and thereby the value of male dairy calves 180 .…”
Section: Genomic Advances Are Uncovering a Growing List Of Target Genmentioning
confidence: 99%
“…Thus far, efforts in editing the genome of livestock have mostly concentrated on largely uncontroversial human health applications, such as generating animal models of human genetic diseases, producing biopharmaceuticals and xenotransplantation. However, genomic and other advances are uncovering a growing list of putative target genes and mutations for which editing has been or is being pursued in order to improve aspects of livestock production 175,178,179 , such as growth rate, muscle mass, meat fat content, milk composition, wool growth, resistance to bacterial, viral and parasitic diseases, temperature tolerance, animal welfare and environmental impact (TAble 3). A specific application that is worth mentioning is the generation of malespecific double-muscling by inserting a trans-acting inhibitor of MSTN on the Y chromosome, which could have a major economic impact by improving the carcass yield and thereby the value of male dairy calves 180 .…”
Section: Genomic Advances Are Uncovering a Growing List Of Target Genmentioning
confidence: 99%
“…New food technologies provide diverse opportunities for that purpose. By using gene technology, for example, the nutrient quality of meat can be improved or animals can be engineered to be more resistant to diseases (Lievens, Petrillo, Querci, & Patak, ). Other technologies, for example, nanotechnology, have advantages such as prolonging food shelf life, which could reduce food waste and thus conserve resources (Chaudhry et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Wall et al (2005) reported transgenic Jersey cows secreting lysostaphin were protected against Staphylococcus aureus mastitis. Listings of the various other works undertaken in the genetic engineering of livestock species can be found in reviews by Laible et al (2015) and Lievens et al (2015).…”
Section: Genetic Engineeringmentioning
confidence: 99%